2019
DOI: 10.5935/abc.20190184
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Unfavourable Outcomes in Children and Adolescents Submitted to Surgical Mitral Valvuloplasty Secondary to Chronic Rheumatic Heart Disease

Abstract: Background: Mitral valve repair in paediatric patients with chronic rheumatic heart disease is superior to valve replacement and has been used with good results.Objective: To identify predictors of unfavourable outcomes in children and adolescents submitted to surgical mitral valvuloplasty secondary to rheumatic heart disease.Methods: Retrospective study of 54 patients under the age of 16 operated at a tertiary paediatric hospital between March 2011 and January 2017. The predictors of risk for unfavourable out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(39 reference statements)
0
7
0
2
Order By: Relevance
“…A study by Khan et al [ 22 ] failed to establish relationship between the type of injury and higher mortality. Likewise, it is not yet well established which associated valve lesions imply the highest surgical risk, although tricuspid regurgitation has already been identified as an independent risk factor for death and morbidity [ 12 , 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Khan et al [ 22 ] failed to establish relationship between the type of injury and higher mortality. Likewise, it is not yet well established which associated valve lesions imply the highest surgical risk, although tricuspid regurgitation has already been identified as an independent risk factor for death and morbidity [ 12 , 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, o reparo da valva mitral permanece sendo uma estratégia razoável para DCR em idades mais jovens. 218 …”
Section: Utilização E Custo Da Atenção à Saúdeunclassified
“…Thus, probably, the choice of the type of prosthesis was based not only on technical but also on socioeconomic issues, and the decision was made by the medical staff and the patient. Kim et al 16 and Cruz et al 36 have demonstrated severe tricuspid regurgitation as a risk factor, and Rankin et al 22 and De Bacco et al, 32 respectively, have identified a history of previous valve surgery, and urgency of surgery as risk factors. Elevated cardiopulmonary bypass and aortic clamping times have already been described by Bueno et al 29 However, we could not demonstrate such associations, which is in accordance with results reported in other studies.…”
Section: Discussionmentioning
confidence: 99%